2005
DOI: 10.1002/jcla.20053
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of neopterin and interleukin‐2 receptor in women with severe preeclampsia

Abstract: Preeclampsia continues to be a major cause of maternal and perinatal mortality and morbidity worldwide. The etiopathogenesis of preeclampsia is not fully understood. Neopterin and interleukin-2 (IL-2) production reflects cellular immunity. Our purpose was to determine the levels of neopterin and interleukin-2 receptor (IL-2R) in pregnant women with severe preeclampsia, and assess the implications of these findings in the pathophysiology of preeclampsia. Fourteen women with preeclampsia were compared with 14 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…27 Additional studies have found increases in placental and/or peripheral blood levels of the inflammatory cytokines IL-2, IL-12, IL-15, IL-18, and IFN-γ in hypertensive pregnant women. [28][29][30] In contrast, Freeman et al found that IL-10 and TNF-α serum levels increased from the first to the third trimester in control pregnancies to nearly the same degree as in women with hypertensive pregnancies. 31 These inconclusive and often contradictory findings reveal that our understanding of the factors contributing to hypertensive pregnancies is quite limited and may also represent differences in the etiology (i.e., excessive maternal immune system activation vs. placental insufficiency).…”
Section: Discussionmentioning
confidence: 80%
“…27 Additional studies have found increases in placental and/or peripheral blood levels of the inflammatory cytokines IL-2, IL-12, IL-15, IL-18, and IFN-γ in hypertensive pregnant women. [28][29][30] In contrast, Freeman et al found that IL-10 and TNF-α serum levels increased from the first to the third trimester in control pregnancies to nearly the same degree as in women with hypertensive pregnancies. 31 These inconclusive and often contradictory findings reveal that our understanding of the factors contributing to hypertensive pregnancies is quite limited and may also represent differences in the etiology (i.e., excessive maternal immune system activation vs. placental insufficiency).…”
Section: Discussionmentioning
confidence: 80%
“…28, 29 Similar to our own study, Haeger et al and Kaleli et al reported that plasma NEO concentrations were elevated in women with preeclampsia compared to normal pregnant women. 30 31 In two different studies, Schrocksnadel et al reported that NEO levels are elevated in hypertensive pregnant women. 32, 33 More recent data showed that there were no significant differences in NEO concentrations between normal pregnant women and women with preeclampsia between 18 and 38 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that PDS rats exhibit increased serum levels of the proinflammatory cytokines IL-2, IL-12, and IFN␥ and the chemokine RANTES on gestational day 20 (34), similar to women with PE compared with NP women (4,5,7,16,17,27). Here we report that rats treated with DOCA/saline during pregnancy also exhibit significantly increased serum levels of endothelin-1, which may contribute to the decreased endothelial function and increased systolic blood pressure evident in these rats.…”
Section: Discussionmentioning
confidence: 99%